2014
DOI: 10.3928/00220124-20141023-04
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Education Program to Improve Care of Patients With Dementia in an Acute Care Setting

Abstract: As the population ages, the number of patients with dementia in acute care environments is projected to increase rapidly. However, many acute care nurses have undertaken little or no dementia training, potentially leading to reduced quality of care for these patients. This article details the development and delivery of a tailored education program to improve thhequality of care of patients with dementia in a large, urban hospital in Australia. Designed specifically for the existing context, environment, and k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…In the papers of the remaining nine studies, details of specific aspects of training which participants identified as particularly useful, or which they recommended changing were reported. These included the training being directly relevant to them and their practice (Palmer et al, 2014, Schindel Martin et al, 2016, including strategies or practical tools they could take directly back to their workplace (Galvin et al, 2010, Litvin et al, 2012, Nayton et al, 2014, Palmer et al, 2014, Schindel Martin et al, 2016, Wesson, 2010. The opportunity to experience a placement in a community setting (Banks et al, 2014, Waugh et al, 2011 from two different groups of participants undertaking the same programme and the inclusion of the direct experiences of people with dementia and carers within the programme (Baillie et al, 2016, Ellis, 2008, Waugh et al, 2011 were also identified as impactful.…”
Section: Reactionmentioning
confidence: 99%
“…In the papers of the remaining nine studies, details of specific aspects of training which participants identified as particularly useful, or which they recommended changing were reported. These included the training being directly relevant to them and their practice (Palmer et al, 2014, Schindel Martin et al, 2016, including strategies or practical tools they could take directly back to their workplace (Galvin et al, 2010, Litvin et al, 2012, Nayton et al, 2014, Palmer et al, 2014, Schindel Martin et al, 2016, Wesson, 2010. The opportunity to experience a placement in a community setting (Banks et al, 2014, Waugh et al, 2011 from two different groups of participants undertaking the same programme and the inclusion of the direct experiences of people with dementia and carers within the programme (Baillie et al, 2016, Ellis, 2008, Waugh et al, 2011 were also identified as impactful.…”
Section: Reactionmentioning
confidence: 99%
“…13 However, our search of the literature identified very few experimental studies that have investigated the impact of comprehensive dementia education programs implemented in acute hospital sites. 17,50-52 The studies that have been conducted in the acute sector have methodological limitations or did not provide details on the program content or specific delivery methods. In the single study where delivery methods were well described, content specific to prevention and management of emotional stress experienced by patients with dementia-related NDB was not evident.…”
Section: Literature Reviewmentioning
confidence: 99%
“…17,51,53,54 It is important, therefore, that education for acute hospital personnel goes beyond the neurological and functional changes associated with dementia to include application of dementia communication principles, dementia-specific person-centered strategies, and explanation that NDB arises due to patient stress, unmet needs, and task-focused care delivery. 13,36 The intervention that is the focus of this study was delivered to fill the identified gap.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Six studies included both qualified nursing staff and non-qualified care staff as participants. Three studies (Beattie et al, 2014;Bergland et al, 2015;Lopez et al, 2010) included other staff groups in addition to nurses and care staff. For example, Beattie et al (2014) recruitedcatering staff and activities staff, while Lopez et al (2010) recruited social workers and senior administrators, amongst other professionals.…”
Section: Characteristics and Qualitymentioning
confidence: 99%
“…In terms of quality appraisal (MMAT scores), only one study scored 100% (Pierson, 1999), two studies scored 75% (Bergland et al, 2015;Pasman, 2003), five scored 50% (Akerlund & Norberg, 1985;Athlin et al, 1990;Beattie et al, 2014;Chang & Roberts, 2008;Lopez et al, 2010), and three scored 25% (De Bellis, 2003;Kayser-Jones & Schell, 1997;Michaelsson et al, 1987). The most common unmet criterion across studies was "Is appropriate consideration given to how findings relate to researchers' influence, e.g., through their interactions with participants?…”
Section: Characteristics and Qualitymentioning
confidence: 99%